2019
DOI: 10.1002/jimd.12044
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic hematopoietic stem cell transplantation with myeloablative conditioning for adult cerebral X‐linked adrenoleukodystrophy

Abstract: The adult cerebral form of X‐linked adrenoleukodystrophy (ACALD), an acute inflammatory demyelinating disease, results in a rapidly progressive neurodegeneration, typically leading to severe disability or death within a few years after onset. We have treated 15 men who had developed ACALD with allogeneic hematopoietic stem cell transplantation (HSCT) from matched donors after myeloablative conditioning with busulfan and cyclophosphamide. All patients engrafted and 11 survived (estimated survival 73 ± 11%), 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Moreover, neurological findings attributable to cerebral/cerebellar/brainstem lesions became stable or partially improved in all the 12 patients. Compared with the clinical outcomes in previous studies ( Hitomi et al , 2005 ; Fitzpatrick et al , 2008 ; Saute et al , 2016 ; Kühl et al , 2017 ; Waldhüter et al , 2019 ), the results described in the present report demonstrated outstanding clinical outcomes including arrest of disease progression of the clinical presentations and stabilization of the MRI findings as well as the safety associated with HSCT. The clinical courses of patients with ALD after HSCT were also better than those described in a natural history study ( Suzuki et al , 2005 ).…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Moreover, neurological findings attributable to cerebral/cerebellar/brainstem lesions became stable or partially improved in all the 12 patients. Compared with the clinical outcomes in previous studies ( Hitomi et al , 2005 ; Fitzpatrick et al , 2008 ; Saute et al , 2016 ; Kühl et al , 2017 ; Waldhüter et al , 2019 ), the results described in the present report demonstrated outstanding clinical outcomes including arrest of disease progression of the clinical presentations and stabilization of the MRI findings as well as the safety associated with HSCT. The clinical courses of patients with ALD after HSCT were also better than those described in a natural history study ( Suzuki et al , 2005 ).…”
Section: Discussioncontrasting
confidence: 75%
“…Of the 17 patients, however, three patients showed the progressive enlargement of cerebral lesions or appearance of new lesions >1 year after HSCT and eight patients died because of HSCT-related complications or disease progression ( Hitomi et al , 2005 ; Fitzpatrick et al , 2008 ; Saute et al , 2016 ; Kühl et al , 2017 ). Of the additional seven patients with ACALD recently reported in addition to the eight patients in the previous multicenter-based retrospective study, two patients died because of HSCT-related complications or disease progression ( Waldhüter et al , 2019 ). The source of stem cells was either cord blood or peripheral blood for 4 of the 10 patients who died ( Fitzpatrick et al , 2008 ; Saute et al , 2016 ; Kühl et al , 2017 ; Waldhüter et al , 2019 ), whereas the source of the stem cells in the present study was the bone marrow for all the patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 20% of males with adrenomyeloneuropathy will also develop CALD later in life with the same poor prognosis as in children. The only available therapy for CALD is allogenic HSCT (Raymond et al, 2019;Waldhüter et al, 2019). If performed in patients with minimal brain lesions and no/minor clinical symptoms, it may arrest the progression of demyelinating lesions.…”
Section: Alteration Of Fatty Acid Metabolism In Syndromes Presenting mentioning
confidence: 99%